Editorial: how safe is it to administer the BCG vaccination to babies exposed to anti‐TNFα medications antenatally? Authors' reply. Issue 11 (10th November 2019) - Luu, Maxime; Benzenine, Eric; Barkun, Alan; Doret, Muriel; Michiels, Christophe; Degand, Thibault; Quantin, Catherine; Bardou, Marc
Abstract : LINKED CONTENT This article is linked to Luu et al and Bouri and Hart papers. To view these articles, visit https://doi.org/10.1111/apt.15504 and https://doi.org/10.1111/apt.15535 .